Collagen cryogel cross-linked by naturally derived dialdehyde carboxymethyl cellulose. (20th September 2015) - Tan, Huan; Wu, Bo; Li, Changpeng; Mu, Changdao; Li, Hongli; Lin, Wei
Highlights: The M w of water soluble DCMC is 2.38 × 10 5 g/mol measured by LLS. Incorporation of minute DCMC can induce cross-linked collagen cryogel. Crosslinking reaction and cryogenic treatment do not destroy collagen triple helix. The cryogel has a heterophase structure and displays good biological properties. Abstract: We present the use of a natural derivative, dialdehyde carboxymethyl cellulose (DCMC) as the cross-linker for the preparation of spongy collagen cryogels by freezing-thawing method. The DCMC has been characterized by laser light scattering (LLS), showing the molecular weight of 2.38 × 10 5 g/mol. FT-IR studies demonstrate that the cross-linking reaction and the cryogenic treatment do not destroy the triple helix of collagen. SEM images indicate that the cryogel has a heterophase structure with interconnecting macropores. DSC measurements reveal that the incorporation of a very small amount of DCMC can significantly improve the thermal stability of collagen. Moreover, the cryogels exhibit fast swelling rate, and their equilibrium swelling ratio is related to DCMC content and pH-dependent. The in vitro blood-compatibility tests prove that the introduction of DCMC does not cause the reducing performance in hemolysis and blood clotting compared with pure collagen. Hence, the low-cost and non-toxic nature of DCMC confers the cryogel great potential in tissue engineering and other biomedical applications.